Service chain-based approach for Web service composition - FU Yan-ning; LIU Lei; JIN Cheng-zhi (Tongxin xuebao)
A semantic match-based method was proposed for searching Web service chain by adopting the semantic matching algorithm for service profiles,which is based on the web services ontology and the domain-related ontology.By resorting to this method,a service chain can be found in accordance with the request for service and can be composed in order to serve needs of requests.It shows how to the discovery of the service chain can be done by applying the method mentioned above to a concrete example.